Logistic planning for industrial cities in Jeddah using geometrics techniques: التخطيط اللوجستي لمواقع المدن الصناعية في محافظة جدة باستخدام تقنيات الجيوماتكس - Nada Soliman Abdulaziz Al - Khalifi Al – Enezi (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
This study examined the spatial distribution of the industrial cities in Jeddah governorate, as well as the phases of the industrial cities and the reasons for their development. The study also examined the relationship between the sites of the industrial cities and the transportation methods, and reached through the logistical planning of many proposals for the industrial cities. The study was based on Jeddah satellite satellite Landsat for the year 1440 H / 2018, as well as on geomatics techniques through two programs (Erdas Imagine 2014 / Arcmap10.5). The study concluded with a number of results, the most important of which is that Jeddah has the largest share of the industrial cities with 4 industrial cities. The study recommended distinguishing the new industrial zones with a green belt and setting the penalties so as not to be infringed and thus interfering between the urban scope and the industrial use. In addition to attract investors and stimulate the industrial market through the establishment of facilities for the investor such as loans and assistance in the means of transport for industrial products. The study recommended benefiting from the proposals and urging researchers to activate the role of scientific techniques in solving the problems of urban planning.